Control of wind energy systems - Lim, Wee Liam (Nanyang Technological University, 2021)
Wind energy can be harvested using Wind Turbines Generators which is evidently seen throughout the world. However, the efficiency of energy harvesting systems differs from one another based on their make, type, and design. This variation in designs can be represented using simulation software, thus allowing an in-depth study of Wind Turbines. However, existing research and documentation are often targeted at specific components of a Wind Turbine system. As such, complete representations of the Wind Turbine simulation model are few and far between. Using MATLAB (Simulink) software, a complete wind turbine generator is modelled. This report presents the process of creating a simple Wind Turbine Generator model. An overall simulation under varying wind speed conditions is conducted and concluded in this report. Control methodologies as well as possible areas for future work are also discussed in detail in this report.